LITERACY IN THE LANGUAGE CLASSROOM - Agnes Widyaningrum (Dinamika Bahasa dan Budaya, 2008)
(English) language teaching has so far shifted to a more discourse-oriented paradigm,  resulting in genre-based approaches to the teaching of the four language skills with the development of competency-based curriculum. This paper highlights how literacy should be incorporated in the language classroom in such a way that the primary aim of language teaching is to make the students literate in the socio-cultural settings of the target language. Discussed prior to the curriculum design and program planning is  the theoretical principles which deal with (1) the model of language, (2) relationship between spoken and written language, (3) the term ‘literacy’ and (4) implication of the model of language. Meanwhile, in the curriculum design and program planning  this paper addresses  three major issues, such as (1) the point of departure for program planning, (2) the teaching-learning cycle, and (3) the teaching-learning cycle and classroom planning.